Nature's numbers: expanding the national economic accounts to include the environment - Nordhaus, William D; Kokkelenberg, Edward Charles (National Academy Press, 1999)
In order to really see the forest, what's the best way to count the trees? Understanding how the economy interacts with the environment has important implications for policy, regulatory, and business decisions. How should our national economic accounts recognize the increasing interest in and importance of the environment? Nature's Numbers responds to concerns about how the United States should make these measurements. The book recommends how to incorporate environmental and other non-market measures into the nation's income and product accounts. The panel explores alternative approaches to environmental accounting, including those used in other countries, and addresses thorny issues such as how to measure the stocks of natural resources and how to value non-market activities and assets. Specific applications to subsoil minerals, forests, and clean air show how the general principles can be applied. The analysis and insights provided in this book will be of interest to economists, policymakers, environmental advocates, economics faculty, businesses based on natural resources, and managers concerned with the role of the environment in our economic affairs.